Effects of node number of vine cuttings and planting methods on endogenous hormone contents at nodes and storage root formation in sweet potato - Yiming Song; Zhiqiang He; Guangyan Sun; Shuwen Deng; Zhenpeng Deng; Changwen Lyv; Daobin Tang; Jichun Wang (PLoS ONE, 2026)
As a globally significant dual-purpose crop, sweet potato yield is regulated by the node number of vine cuttings and the planting method. Elucidating the effects of stem segment number and soil-entry method on endogenous hormones within sweet potato nodes and storage root formation holds significant scientific value, providing theoretical basis and technical support for optimizing planting techniques and enhancing yields. A two-factor split-plot design was implemented from 2022 to 2023 using the Yuhongxinshu 98 cultivar. Main plots tested vine cuttings with 6 (A1), 8 (A2), or 10 nodes (A3). Subplots compared slanted planting with exposed tip (B1), flat planting with exposed tip (B2), and flat planting without exposed tip (B3). The study investigated the effects of these treatments on growth hormone content at nodes, root morphology, and yield. Results indicated that increasing vine cutting node number to 8 and 10 significantly enhanced early adventitious root development, including root length, root diameter, and root tip number, and increased aboveground branching. Compared with 6-node cuttings, 8- and 10-node cuttings increased storage root yield by 23.43% and 30.03%, respectively. Compared with slanting planting with exposed tip, flat planting with exposed tip and flat planting without exposed tip increased storage root yield by 20.11% and 18.10%, respectively. At 70 DAT, corresponding to the early storage root enlargement stage, ABA and IAA contents in buried nodes increased with vine cutting node number. IAA content showed a node-dependent pattern and peaked at the fourth buried node, whereas ABA content was highest at the second buried node. Correlation analysis showed that ABA and IAA contents were associated with storage root yield, storage root number, and root morphological traits. Nodal analysis indicated that storage root formation was mainly concentrated in the upper buried nodes, especially the second buried node, while flat planting increased the contribution of multiple buried nodes to storage root formation. Overall, 8-node vine cuttings combined with flat planting, especially A2B2 and A2B3, showed better performance in coordinating early root establishment, nodal storage root formation, and yield improvement. These findings provide a practical basis for optimizing sweet potato planting techniques through improved vine cutting node number and planting method.